KONSEP MUSIK RAHAYU SUPANGGAH DALAM TEATER I LAGALIGO - Danis Sugiyanto (Institut Seni Indonesia Surakarta, 2009)
I Lagaligo (ILG) epic belongs not only to Sulawesi society anymore but to the world as well. The epic contains many values of life such as history, literature, philosophy of life, humanity, and so on. The epic has been talked about as the latest performing art dealing with such problems as East-West culture, collaboration, originality, morality, and so on. This writing analysis (ILG) in detail covering the people (artists) involved in the production of ILG musical theatre, how ILG musical theatre could be performed in various world class festivals, and the explanation of Rahayu Supanggah’s concepts of musical theatre in ILG and music director’s views. Key words : i lagaligo, concept of ILG musical theatre, Rahayu Supanggah